Physical activity status, nutrient intake, menstrual and bone status in overweight and obese women during the covid-19 pandemic lockdown 2.0 in Malaysia - Raof, Nur Dalila Adilah Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Objective: This study investigated the relationship between physical activity status, nutrients intake (Carbohydrate, Protein, Fats, Sugar, Vitamin C, Vitamin D, Vitamin K, Calcium, Potassium, Phosphorus), menstrual and bone status [previous bone physical activity questionnaires in the past 12 months (pBPAQ) and current bone physical activity questionnaires (cBPAQ)] in overweight and obese women during the COVID-19 Pandemic Lockdown 2.0. Methods: Thirty-six female participants from Universiti Sains Malaysia who are overweight and obese women (age: 24.1 ± 5.0 years old; weight: 72.7 ± 11.2 kg; BMI: 28.8 ± 3.0 kg/m2) were recruited in this study. Participants were required to answer several questionnaires, i.e. Physical Activity Readiness Questionnaire (PAR-Q), Menstrual History Questionnaire, Bone Physical Activity Questionnaire (BPAQ) and 24-Hours Diet Recall. Participant’s anthropometry parameters, body height, body weight, body mass index (BMI) and fat free mass (FFM) were recorded. Correlation and stepwise regression were used for statistical analysis. Results: During lockdown 2.0, the total calories intakes of the participants was 1319.64 ± 562.16 kcal/day and most of the dietary intake met the recommended nutrient intake (RNI) except for carbohydrate, sugar, Vitamin C, Vitamin D, calcium, potassium and phosphorus. Participants were reported to have sedentary lifestyle. Past BPAQ score of the participants is 21.8 ± 28.6 while current BPAQ score is 23.4 ± 38.9. Both past and current bone status of the participants are considered as poor as their BPAQ scores were less than40. On average, participants were categorised as eumenorrhea and healthy. Overall, fat free mass had a significant relationship (p < 0.001) with total calories intakes. The total calories intakes had a positive correlation with current bone status cBPAQ (p<0.001) and menses days (p<0.05). Nevertheless, participants’ days between menses had a significant negative association with body weight (kg) (p<0.05) and fat free mass (kg) (p<0.05). Frequency of menses (in the past 12 months) also had a significant positive association with calcium (p<0.05) and phosphorus intakes (p<0.05) respectively, while carbohydrate had a significant correlation with current bone status (cBPAQ) (p<0.001) and menses days (p<0.05). Protein and calcium intakes had a positive association with frequency of menses (in the past 12 months) (p<0.05). Meanwhile, fats had a correlation with current bone status (cBPAQ) (p<0.05) and menses days (p<0.05) respectively. No significant association found in sugar and other minerals like Vitamin C, Vitamin D, Vitamin K and potassium for all parameters. In addition, bone status in the past 12 months (pBPAQ) showed a significant relationship with current bone status (cBPAQ). Conclusion: Generally, nutrient intake and physical activity was lower than recommended during this pandemic during lockdown 2.0. Total calorie of the participants also lower than recommended, and the time spent on sedentary behaviours was increased. Normal menstrual cycle was found to be depending on total calories intake, macronutrients (carbohydrate, fat and protein) and also minerals such as calcium and phosphorus. In addition, it is important to maintain ideal body weight (normal body weight and high of fat free mass) as it influences menstrual cycle, and macronutrients intakes as it influences bone status. Physical activity that related with high impact exercises also could be beneficial to affect bone status in later life.